Pengaruh Psikokuratif terhadap Kadar VEGF-c, Kortisol dan Skor HADS Pasien Kanker Serviks Stadium Lanjut - Soetrisno, Soetrisno; Sulistyowati, Sri; Tjiang, Rubin Enhui; Wujoso, Hari; Nurinasari, Hafi; Cahyanto, Erindra Budi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Cancer diagnosis and therapy that causes chronic stress, its progression to depression increase cortisol and VEGF-c levels in advanced cervical cancer patientsObjective: To know the VEGF-c, cortisol and HADS level in advanced stage cervical cancer patients who get Psychocurative intervention Method : An experimental study of pretest – posttest controle group design in outpatient oncology clinic and ward of Doctor Moewardi General Hospital. Thirty subjects with advanced cervical cancer were randomly divided into 15 patients in the intervention group, and 15 in control. Psycho-curative intervention 4 times a month, 1 time a week, 60 minutes duration. Before and after intervention, each subject of the two groups was examined levels of VEGF-c, cortisol and HADS scores. Data obtained were analyzed by independent t test, Mann Whitney, Pair t and Wilcoxon with the 19th version of SPSS for Windows.Result and Discussion: Average VEGF-c levels before intervention 9006.53 ± 2181.49, after intervention 5631.20 ± 2071.55, p <0.001. The mean cortisol level before intervention was 12.29 ± 4.36, after intervention 6.71 ± 3.88, p <0.001. The mean HADS Anxiety score before intervention was 14.13 ± 3.02, after intervention 8.47 ± 3.07, p <0.001. Mean Depression HADS scores before intervention 13.80 ± 3.21, after intervention 7.20 ± 2.70, p <0.001.Conclusion : VEGF-c levels, cortisol, HADS anxiety scores and depression in patients with advanced cervical cancer decline after psychocurative intervention. Keywords : Psychocurative; VEGF-c; Cortisol; HADS; Cervical cancer